The Bird Community in an Oil Palm Landscape Containing Small Forest Fragments - Voon, Audrey Mei Fang (2019)
Most forest fragments in the oil palm plantation are remnants of unsuitable area for establishing oil palm estates. These areas consist of low diversity, density of birds because of its small area and isolated from large pristine forest. Studying bird ecology is essential in perceiving ecological complexity and quality in an area. In this study, bird species richness, abundance, and community composition were examined for the variations, from interior forest habitats and their edges into adjacent oil palm plantation in Bintulu for 13 months. Mist-netting method resulted in 342 individuals with 58 species and 23 families with 45 sampling days (completeness ratio= 0.766) whereas point count census resulted in 1954 observations that consisted of 33 families that were represented by 103 species in 286 observational hours (completeness ratio= 0.85). For mist-netting method, the highest number of bird species recorded was Little Spiderhunter (Arachnothera longirostra) with 43 individuals (12.57% from all the bird captured in this study) followed by Oriental Magpie Robin (Copsychus saularis) recorded with 38 individuals (11.11%) and Rufous-backed Kingfisher (Ceyx erithaca) recorded with 36 individuals (10.53%). For point-count census, sampling saturation was achieved on survey on day 30 as the species accumulation curve has reached an asymptote. The most frequently recorded bird species by using point count census was Oriental Magpie Robin (Copsychus saularis) (326 observations, 16.68% from the total bird observed in this study) followed by Rufous-tailed Tailorbird (Orthotomus sericeus) (152 observations, 7.78%) and Yellow-vented Bulbul (Pycnonotus goiavier) (129 observations, 6.6%). Transient species were eliminated from the analysis. Shannon diversity and evenness indices calculated for overall bird recorded in the study area was H= 3.751 and EH = 0.37, respectively. Diversity index of birds in the forest (H= 3.769) was significantly higher compared to the edge (H=3.386) and oil palm plantation (H= 2.198). Species evenness index in the forest was higher (EH= 0.5419) than the oil palm plantation (EH= 0.3752) and edge (EH= 0.4688). Besides, overall density of bird was estimated to 33.78 individual/hectare (SE= ±2.06, CVoverall=0.061, effective detection radius (EDR)= 19.48m). Other than that, bird density in the forest area is 23.214 individual/hectare (SE= ±1.9653, CVforest= 0.067), followed by the edge 40.159 individual/hectare (SE= ±2.6904, CVedge= 0.085), while in the oil palm plantation was 30.017 individual/hectare (SE= ±2.09892, CVplantation= 0.07). The edge zone was the most populated area when compared with the forest and the oil palm plantation. The effect of seasonality is apparent when most birds were recorded in January with relatively high diversity (H= 3.326). Insectivores were most dominant, followed by frugivore-insectivore. The forest and oil palm plantation were dominated by insectivorous (46%) followed by frugivore-insectivorous (20.87%) and the least is granivore (1.74%). Systematic surveys on the avian assemblage structure in forest fragments near the oil palm plantation is important as it would provide indication on the quality of the habitat. Long-term sustainability in maintaining and monitoring these bird species which act as pollinators and insect regulators.